Blast from the past [videorecording (DVD)] - Wilson, Hugh, 1943-2018; Fraser, Brendan, 1968-; Walken, Christopher, 1943-; Spacek, Sissy; Silverstone, Alicia (New Line Home Video, 1999)
After being raised in a bomb shelter for 35 years by his parents, Adam emerges into the modern world of Los Angeles.